CT and MR imaging of unusual locations of extra-adrenal paragangliomas (pheochromocytomas). - Sahdev, A; Sohaib, A; Monson, J; Grossman, AB; Chew, S; Reznek, R (2005)
Our review was undertaken to describe CT and MRI features of unusual extra-adrenal paragangliomas (pheochromocytomas). We retrospectively reviewed CT and MRI findings in 29 patients with 39 extra-adrenal paragangliomas. For each tumour, site, size, MRI characteristics, CT appearances and enhancement after gadolinium and iohexol were recorded. There were 17 carotid body tumours, 1 mediastinal, 1 intra-cardiac, 15 retroperitoneal extra-adrenal paragangliomas, 2 bladder, 1 pelvic sidewall and 2 intra-spinal paragangliomas within the lumbo-sacral spine. All 39 paragangliomas were shown on MRI. Of the 32 lesions studied by MRI and CT, CT detected 30. Of the two lesions missed on CT, one was an intra-cardiac paraganglioma and the second a bladder wall paraganglioma. At detection, 25 tumours were larger than 4 cm, of which 20 were heterogeneous lesions on CT and MRI with variable contrast enhancement. The 14 smaller paragangliomas were smooth in contour and demonstrated avid, homogeneous contrast enhancement. Our review of extra-adrenal paragangliomas highlights their unusual sites and appearances. MRI demonstrated the greatest variability in the appearances of larger tumours, provided additional information compared to CT for surgical planning and is a useful screening tool for patients at high risk of extra-adrenal paragangliomas.